Seasonality in maternal intake and activity influence offspring’s birth size among rural Indian mothers—Pune Maternal Nutrition Study - Rao, Shobha (2009)
BACKGROUND: Farming populations from developing countries are exposed to seasonal energy stress due to variations in food availability and energy output related to agricultural activities. This study aims to examine the impact of seasonality in maternal intake and activity on neonatal size. METHODS: Maternal anthropometry, dietary intakes (24-h recall and food-frequency questionnaire) and activity pattern (questionnaire) at 18±2 and 28±2 weeks gestation, and neonatal anthropometry, were measured in a prospective study of 797 rural Indian women. RESULTS: Maternal energy and protein intakes were inadequate (70% of recommended dietary allowance). Both intake and activity showed seasonal variation (P=0.001), with peak values in winter i.e. during harvest, at 18 weeks (median energy 1863 kcal/day, protein 47.5 g/day) and 28 weeks (median energy 1687 kcal/day, protein 43.7 g/day), coinciding with the maximum maternal activity (median score 86.1 at 18 weeks and 79.5 at 28 weeks). Mean birth weight and length (adjusted for pre-pregnant weight, parity, gestation and sex) of babies was highest in summer (peak at February 2733 g, 48.6 cm, respectively) and lowest in winter (nadir at January 2591 g, 47.1 cm, respectively). Regression analysis showed that maternal intake at 18th week had a positive association (P=0.05), maternal activity at 28th week had a negative association (P=0.002) and exposure (in weeks) to winter during gestation had a positive association (P=0.04) with birth size. Furthermore, higher maternal intakes, coupled with lower maternal activity in late gestation were associated with higher birth weight, especially during winter. CONCLUSIONS: If causal, these observations indicate that complete exposure (16 weeks) to the winter season (harvest-time) in late gestation could increase birth weight by 90 g in poor farming communities in rural India, and the benefit would increase further by lowering maternal activity. Our results underscore the importance of considering seasonality in planning targeted intervention strategies in such settings.